TRANSFORMATION OF EDUCATION IN ELEMENTARY SCHOOLS: UTILIZATION OF ARTIFICIAL INTELLIGENCE-BASED LEARNING MEDIA IN THE DIGITAL ERA - Mukti, Fajar Dwi (Pendidikan Guru Madrasah Ibtidaiyah Institut Agama Islam Negeri Padangsidimpuan, 2023)
The study titled